ByzRev 03.2021.014: Robert E. Bjork, Catastrophes and the Apocalyptic in the Middle Ages and Renaissance: (Arizona Studies in the Middle Ages and the Renaissance 43). Turnhout: Brepols 2019. - Kraft, András (The Byzantine Review, 2021)
Robert E. Bjork, Catastrophes and the Apocalyptic in the Middle Ages and Renaissance (Arizona Studies in the Middle Ages and the Renaissance 43). Turnhout: Brepols 2019. xii, 207 pp. – ISBN: 978-2-503-58297-9 (€ 70.00)